TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PENCANTUMAN LABEL HALAL TANPA SERTIFIKAT HALAL PADA RUMAH POTONG AYAM(Studi Kasus Rumah Potong Unggas PORUTUM Kelurahan Mamboro Kecamatan Palu Utara) - Moh. Albar; Andini Asmarini (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to examine the practice of halal labeling without official halal certification at a poultry slaughterhouse in Mamboro, North Palu. In Indonesia, halal certification is regulated under Law No. 33 of 2014 concerning Halal Product Assurance. The issue arises when businesses label their products as halal without going through the official certification process. This research employs a qualitative descriptive method through observation, interviews, and documentation. Findings indicate that business owners apply halal labels based on personal religious confidence without understanding the legal certification process. This practice potentially misleads consumers and contradicts Islamic economic principles of justice (al-‘Adalah) and honesty (ash-Shidq). The study recommends awareness campaigns and stricter enforcement from authorities.